Efficient Removal of PFASs Using Photocatalysis, Membrane Separation and Photocatalytic Membrane Reactors - Nonhle Siphelele Neliswa Mabaso; Charmaine Sesethu Tshangana; Adolph Anga Muleja (Membranes, 2024)
Perfluoroalkyl and polyfluoroalkyl substances (PFASs) are persistent compounds characterized by stable C−F bonds giving them high thermal and chemical stability. Numerous studies have highlighted the presence of PFASs in the environment, surface waters and animals and humans. Exposure to these chemicals has been found to cause various health effects and has necessitated the need to develop methods to remove them from the environment. To date, the use of photocatalytic degradation and membrane separation to remove PFASs from water has been widely studied; however, these methods have drawbacks hindering them from being applied at full scale, including the recovery of the photocatalyst, uneven light distribution and membrane fouling. Therefore, to overcome some of these challenges, there has been research involving the coupling of photocatalysis and membrane separation to form photocatalytic membrane reactors which facilitate in the recovery of the photocatalyst, ensuring even light distribution and mitigating fouling. This review not only highlights recent advancements in the removal of PFASs using photocatalysis and membrane separation but also provides comprehensive information on the integration of photocatalysis and membrane separation to form photocatalytic membrane reactors. It emphasizes the performance of immobilized and slurry systems in PFAS removal while also addressing the associated challenges and offering recommendations for improvement. Factors influencing the performance of these methods will be comprehensively discussed, as well as the nanomaterials used for each technology. Additionally, knowledge gaps regarding the removal of PFASs using integrated photocatalytic membrane systems will be addressed, along with a comprehensive discussion on how these technologies can be applied in real-world applications.